KRITIK ZIAUDDIN SARDAR TERHADAP MUSLIM FUNDAMENTALIS - Rukmaniyah Rukmaniyah (UIN Sunan Kalijaga Yogyakarta, 2015)
This article is an exploration towards one of Ziauddin Sardar ideas, i.e. his critics to the fundamentalist Muslim. Inthe contemporaries Islamic studies, Ziauddin Sardar is well known as writer, poet, and cultural pundit. According to Sardar, in this article, there are some aspects within the fundamentalist Muslim that need to be criticized, i.e. the problem of ethics, the taqlid's paradigm that they developed, and their concept of jihad. More over according to Sardar, as the solution to the problems of contemporary Islamic communities, including the spread of this fundamentalists Muslim, the Islamic world need more an effort of civilization reconstruction (not awakening) that conducted based on 'Islamic World view'.